Geografía Organización del espacio mundial - BARROS, Claudia coord. (ESTRADA, 1999)
CONTENIDO : ALVARADO QUETGLES, RAQUEL; DOMINGUEZ ROCA, LUIS; GENTILE, ELVIRA; GONZALEZ, SILVIA G.; GUTIERREZ, ANDREA I.; PEDONE, CLAUDIA; ZUSMAN, PERLA